BRIDGING 21ST-CENTURY SKILLS AND PANCASILA VALUES: INSIGHTS FROM THE IMPLEMENTATION OF THE P5 PROJECT IN INDONESIAN EDUCATION - Amiruddin, Amiruddin; Sugianto, Roni; Muhammad, Jagad; Rahman, Zainur; Seituni, Siti (Journal on Research and Review of Educational Innovation, 2024)
This study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) as part of the Independent Curriculum in supporting the development of student creativity. The P5 program is designed to build character, critical thinking abilities, and 21st-century skills through a holistic, project-based approach. This study uses the Systematic Literature Review (SLR) method to identify, evaluate, and synthesize research relevant to related questions or phenomena. Data is collected through three main stages of SLR: planning, implementation, and completion. The study results show that the optimal implementation of P5 can increase students' innovation, creativity, and ability to solve problems independently. However, several obstacles are still found, such as the lack of teachers' understanding of the P5 concept, the limitations of supporting facilities, and the diversity of student backgrounds. To overcome this, additional steps are needed, such as teacher training and improving facilities to maximize the effectiveness of P5 in forming a creative generation that has character according to Pancasila values.